Health as a value for diabetic patients - Derkacz, Marek; Chmiel-Perzyńska, Iwona; Grywalska, Ewelina; Nowakowski, Andrzej (Current Problems of Psychiatry, 2012)
Introduction: Health is a multidimensional phenomenon encompassing interdependent physical, mental and social aspects. Understanding the nature and value of health, as well as placing it in the hierarchy of life values, plays a substantial role in the life of every man. Study goal: The assessment of health behaviours and understanding of health as a personal value and the symbol of happiness among patients with type 2 diabetes. Material and methodology: The study was conducted on a group of 50 patients (22 males i 28 females). The average age of the population studied was 58.8 (±15.2) years and the average duration of the disease was 11.4 (±8.6) years. The research tools used in the study included: an original questionnaire, the Health Behaviour Inventory (HBI) and the List of Personal Values (LPV) developed by Zygrfyd Juczyński. Study results: In the case of diabetic patients, among the categories of health behaviour the severity indices for each category were higher in comparison with established standards. The health behaviour index in the study group was 89.3 ± 15. A positive correlation was revealed between education and the results obtained in categories of “eating habits” (p <0.05) and “positive mental attitude” (p <0.001), whereas in the category of “preventive behaviour” (p <0.001) a negative correlation was observed. Women assessed good health higher and both physical and mental fitness as values determining happiness; 67.85% of female respondents considered these features as the most important symbols of happiness compared with 27.27% men (p <0.05). Among the symbols of happiness patients with diabetes listed health in the first place, whereas among the personal values determining personal happiness they listed it on the second place. Conclusion: Diabetic patients give a higher priority to health behaviours compared with healthy subjects. "Good health" is a significant value determining their personal happiness.